Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbasis Audiovisual Terhadap Kemampuan Berpikir Kritis IPAS Peserta Didik Kelas V Sekolah Dasar - Arya Wirayuda, Muhamad; Pangestu, Deviyanti; Nurjanah, Siti; Sowiyah (UNIB Press, 2025)
The research problem was the low critical thinking skills in Science and Social Studies (IPAS) learning among fifth-grade elementary school students due to the teacher’s suboptimal use of learning models. This study aimed to examine the effect of an audiovisual-based guided inquiry learning model on the critical thinking skills of fifth-grade students in IPAS. The research method used was a quasi-experiment with a non-equivalent control group design. The sample consisted of 21 students from class VB and 22 students from class VA. Data were collected through tests and non-test techniques, including observation, interviews, and documentation. The results indicated a significant effect of the audiovisual-based guided inquiry learning model on the critical thinking skills in IPAS among fifth-grade students at SD Negeri 4 Metro Utara.